Between citizenship and human rights: the struggle for justice after Indonesia’s 1965 mass violence - Hearman, Vannessa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
Since the authoritarian New Order regime ended in May 1998, human rights activists and survivors have campaigned for successive governments in Indonesia to address the needs of survivors of the 1965–1966 anti-communist violence. The article traces the changing strategies of activists and survivors in this campaign. In the early democratic period from 1998 to 2004, Indonesian activists sought to transform ideas of citizenship into an inclusive one, embracing and restoring the rights of former political prisoners. However, Indonesian government inaction on past human rights abuses forced them to reconsider their strategy. It propelled them back to a historical practice under the New Order of calling on external allies, including international human rights organizations, to highlight the state’s failure to protect citizens’ rights. The reliance on international partners and norms, however, also implies accepting a limitation on the ambition of human rights activism, since enforcement remains in national governments’ hands.